Exploring autonomous language learning behaviors through video sharing and online discussions in higher education - Olaya, Marian; Mora, Willian (Colombian Applied Linguistics Journal, 2022)
This current study explores how video sharing and online discussions promote learning autonomy in English language classes in a public university for the duration of the quarantine established by the Colombian government during the coronavirus pandemic. This study was conducted with 127 engineering and administration undergraduates from a public university in the department of Boyacá. This was a qualitative case study which intended to identify the extent video sharing and online discussions increase learner’s autonomy behaviors in English language learning .The instruments for data collection were student journal, student artifact, including video recordings and online discussions, interviews, and questionnaires. An open coding analysis was utilized and the results revealed that the degree of autonomous behaviors gradually could be fostered by the implementation of video sharing. Results also indicated that students are receptive to online writing discussions and showed how motivation plays a vital role in learning English and the achievement of own learning goals.